An experimental model to analyse the risk of introduction of a duck-originated H5 low-pathogenic avian influenza virus in poultry through close contact and contaminative transmission - CLAES, G.; MARCHÉ, S.; DEWULF, J.; VAN DEN BERG, T.; LAMBRECHT, B. (Epidemiology and infection, 2014)
Aquatic wild birds are often carriers of low-pathogenic avian influenza viruses (LPAIVs). If H5 and H7 LPAIVs are transmitted to poultry and have the opportunity to circulate, a highly pathogenic AIV may arise. Contact with aquatic wild birds is one of the most important ways in which these LPAIVs can be introduced into poultry flocks. In this study, the transmissibility of a duck-originated H5 LPAIV between ducks and chickens was analysed in a series of animal experiments, using different transmission routes. Results indicate that the outcome of virus intake by chickens exposed to infectious ducks depends on the way the virus is presented. Faecally contaminated drinking water proved to be the most efficient route by which the virus can be transmitted to chickens. The results from this study also suggest that some duck-originated H5 LPAIVs may be introduced to poultry but do not have the potential to become established in poultry populations.